Determinants of Big and Medium Industrial Manufacturing Agglomeration in West Java Province - Nur Annisa Karima; Lilis Siti Badriah; Diah Setyorini Gunawan (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2021)
The aims of this research are to analyze whether or not the manufacture industrial agglomeration in West Java Province and to analyze the factors that can affect the agglomeration especially manufacture industrial agglomeration in West Java Province. This research using Hoover Balassa Index and panel data regression with time period data 6 years (2014-2019) and 27 regencies/cities as cross-section data. The results of this research are : (1) there is no manufacture industrial agglomeration in West Java Province, (2) gross regional domestic product has a negative effect on manufacture industrial agglomeration, (3) minimum wage has a positive effect on manufacture industrial agglomeration, (4) population has a negative effect on manufacture industrial agglomeration. As an implication of the conclusion above, every province or regency/city should seek and make their region as a pole of the agglomeration and the effort that can be done are create some regulations which can support industrial establishment and development easier, giving the information about business and capital, create some regulations about wage, building partnership among companies to create backward and forward linkage.Keywords: Agglomeration, Hoover Balassa Index, Concentration Index